KEMAMPUAN CRITICAL THINKING DAN HASIL BELAJAR KELAS IV SD TINGKIR TENGAH 02 - susilo rudi; Henny Dewi Koeswanti; Sri Giarti (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
This study aims to improve critical thinking skills and mathematics learning outcomes of fourth-grade students of SD Tingkir Tengah 02 Salatiga in the second semester of the 2018/2019 academic year. Critical thinking and learning outcomes are low because the teacher uses the lecture method. The author chooses the Open-Ended model assisted by powerpoint media as a solution. Research procedures include planning, action, observation, and reflection. The results showed an increase from the initial condition with 9 students or 25.71% completed and 29 students or 74.29% not complete. The implementation of the first cycle results obtained 29 students or 82.86% completed and 6 students or 17.14% did not complete. Cycle II as a follow-up and improvement of the first cycle with the acquisition of achieving attainment of 35 students or 100%. The results obtained by the conclusion of the application of Open-Ended learning assisted by powerpoint media can improve critical thinking skills and mathematics learning outcomes of fourth-grade students of SD Tingkir Tengah 02 Salatiga second semester of the 2018/2019 academic year.